Southwest Research-Extension Center, Field Day 1995 (Kansas Agricultural Experiment Station Research Reports, 1995)
Report of agricultural research from Southwest Research-Extension Center of Kansas State University.
Keywords: 1995; SRP739; crops; tillage; irrigation; insect control; weed science